Mast Cell-Mediated and Associated Disorders in Pregnancy: A Risky Game with an Uncertain Outcome? - Woidacki, Katja; Zenclussen, Ana Claudia; Siebenhaar, Frank (Frontiers in Immunology, 2014)
During pregnancy the maternal organism is under the influence of tremendous endocrine as well as immunological changes as an adaption to the implanted and developing fetus. In most cases, the maternal adaptations to pregnancy ensure both, the protection against harmful pathogens and the tolerance towards the growing semi-allogeneic fetus. However, under certain circumstances the unique hormonal milieu during pregnancy is causative of a shift into an unfavorable direction. Of particular importance are cellular disorders previous to pregnancy that involve cell types known for their susceptibility to hormones. One interesting cell type is the mast cell (MC), one of the key figures in allergic disorders. While physiological numbers of MCs were shown to positively influence pregnancy outcome, at least in mouse models, uncontrolled augmentations in quantity and/or activation can lead to pregnancy complications. Women that have the desire of getting pregnant and been diagnosed with MC mediated disorders such as urticaria and mastocytosis or chronic inflammatory diseases in which MCs are involved, including atopic dermatitis, asthma or psoriasis, may benefit from specialized medical assistance to ensure a positive pregnancy outcome. In the present review we address the course of pregnancy in women affected by MC mediated or associated disorders.